Private indebtedness and the banking crisis in Finland - Anne Brunila; Kari Takala (Bank of Finland, 1993)
In Finland the private sector borrowing started to rise rapidly in conjunction with the liberalization of capital movements and deregulation of the domestic financial sector during the second half of the 1980s. The financial deregulation coincided with and amplified an economic boom marked by favourable income expectations, loose fiscal policy associated with improved terms of trade and anticipated reduction in income tax rates. All these factors contributed to the overheating of the Finnish economy that finally turned into a severe recession in the beginning of 1990s. The reaction of households to financial deregulation in Finland was similar to that in the other Nordic countries. As in Norway and Sweden, household indebtedness started to rise in the mid-1980s, after the abolishment of lending rate regulations and prior savings requirements for housing loans. Measured by the ratio of household debt to annual disposable income, household indebtedness peaked in 1990 at more than 80 per cent of annual disposable income. Since then, it has fallen slightly. Debt financing in the corporate sector started to increase rapidly in conjunction with the liberalization of capital movements, which enabled firms also in the domestic sector to raise loans in foreign currencies. During the 1980s debt financing grew most in the real estate business, construction and services. Despite increased borrowing, the debt with respect to equity of Finnish firms did not rise significantly until 1990-91, because a large part of the debt growth was matched by increases in corporate earnings and equity values during the late 1980s. Recession turned the situation for the worse as corporate earnings and the market value of assets plummeted. High indebtedness and overcapacity especially in the domestic sector will require several years of adjusting.
URN:NBN:fi:bof-201908121390
Keywords: 330